Patient factors that predict admission to an emergency psychiatric unit following deliberate self-harm in an urban hospital in South Africa - Grobler, Kathryn (Department of Psychiatry and Mental Health, 2021)
Background: Suicidal behaviour is increasingly widespread in South Africa and constitutes a significant burden of disease, often within resource-constrained hospital settings. Little is known about the factors associated with psychiatric admission following an act of deliberate self-harm (DSH) in South Africa. Aim: The aim of this study was to investigate the sociodemographic and clinical factors which differentiated DSH patients who were admitted to an emergency psychiatric unit compared to those who were treated in the emergency department and discharged. Setting: Data were collected for 272 consecutive patients presenting to the emergency department of a tertiary, public, urban hospital in South Africa, as a result of self harm, between 16 June 2014 and 29 March 2015, for an initial epidemiological study of DSH at the hospital. This study had a data subset of 174 of those patients (84 admitted to the emergency psychiatric unit and 90 treated in the emergency department and discharged). Methods: This study was a retrospective cross-sectional analysis, and it analysed existing data from the epidemiological study, using bivariate and multivariate logistic regression analysis. Results: Of the patients admitted to the emergency psychiatric unit, a greater proportion of patients were female (61,9%), were not in a relationship (83,3%), had no dependents (60,7%), were unemployed (73,8%), and had a low socioeconomic status (59,5%). Having dependants was associated with an increased likelihood of admission to the emergency psychiatric unit in bivariate analysis; however, when controlling for other sociodemographic variables, this was no longer significant. None of the clinical variables were significantly associated with admission to the emergency psychiatric unit. Conclusion: The lack of significant findings in the sociodemographic and clinical factors associated with an admission to the emergency psychiatric unit (compared to being treated in the emergency department and discharged) is surprising. At face value, it suggests that there are no obvious differences between the two groups. The use of a validated screening tool or more accurate measure of the clinical correlates (e.g. screening tool for substance-related 6 disorders) could have better highlighted, perhaps subtle, differences between the two groups. It is perhaps more important to question whether the perceived risk factors in DSH patients are associated with suicidal behaviour and whether emergency psychiatric unit admission, based on these factors, is more effective at treating DSH short-term, and reducing suicidal behaviour long-term, than say outpatient-based treatment interventions. Clinician-related factors that influence psychiatric admission decisions following DSH is also an important area for future research.